Posterior Fossa Tumors in Pediatric Age Group, an Epidemiological Study (Bangladesh Journal of Neurosurgery, 2021)
Background: There are no data so far relating posterior fossa brain tumors in pediatric age group in Bangladesh. We are dealing with this type of tumors regularly. So an attempt has been made to document these tumors in respect to their incidence in our country, mode of presentation, age and sex distribution, treatment offered to them and their complication and outcome.Methods: This study was conducted in the Department of Pediatric Neurosurgery, National Institute of Neurosciences and Hospital. It was a retrospective study and cases were collected from 2013-2020.Result: We dealt with 60 cases of posterior fossa brain tumors. Out of them 21 were medulloblastoma,19 pilocytic astrocytoma, 11ependymoma and rest are other tumors. Almost all patients presented with hydrocephalus and in most cases CSF diversion was done before definitive tumors surgery.Conclusion: This is only a partial picture of total posterior fossa tumors in pediatric age group. This type of study should be done in a larger scale and newer modalities of diagnostics should be widely practiced for a better post-operative treatment and better prognosis.Bang. J Neurosurgery 2021; 10(2): 182-184